2015
DOI: 10.3109/00207454.2015.1038712
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in 188 patients with myasthenia gravis in China

Abstract: Myasthenia gravis (MG) is a kind of chronic autoimmune disease which can weaken patients' motor function and, furthermore, produce negative impact on the health-related quality of life (HRQoL). The primary purpose of this research was to evaluate factors that might affect the HRQoL of MG patients. A cross-sectional clinical research was carried out including 188 successive patients with MG. Myasthenia Gravis Foundation of America (MGFA) classification and Quantitative Myasthenia Gravis (QMG) score were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 35 publications
4
35
2
1
Order By: Relevance
“…Considering the interferences of daily functioning due to the symptoms of MG, heightened depression and lowered quality of life (QOL) are not unanticipated [ 4 12 ]. Disease’s severity [ 4 ], lower education [ 5 ], older age [ 5 6 ], being woman [ 7 ], as well as lower social support [ 5 ] were positively correlated with patient’s physical health [ 4 7 ], while being optimistic, positive thinking, and sense of humor functioned as protective factors [ 8 ] for a better QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the interferences of daily functioning due to the symptoms of MG, heightened depression and lowered quality of life (QOL) are not unanticipated [ 4 12 ]. Disease’s severity [ 4 ], lower education [ 5 ], older age [ 5 6 ], being woman [ 7 ], as well as lower social support [ 5 ] were positively correlated with patient’s physical health [ 4 7 ], while being optimistic, positive thinking, and sense of humor functioned as protective factors [ 8 ] for a better QOL.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the search, 9 cross-sectional studies were identified that assessed the quality of life of patients with GMG; however, no specific evidence was identified for the subtype of refractory GMG. In most of the included studies, comparisons are made between different types of MG, identifying a greater impact on the quality of life in GMG versus ocular MG and MG in remission (10,13,14). The differences are especially found in the domains of physical function, physical role, bodily pain, vitality and social function (13).…”
Section: Discussionmentioning
confidence: 99%
“…In most of the included studies, comparisons are made between different types of MG, identifying a greater impact on the quality of life in GMG versus ocular MG and MG in remission (10,13,14). The differences are especially found in the domains of physical function, physical role, bodily pain, vitality and social function (13). The connection of the domains of quality of life may be related to that found by Oosterhuis H, in his study of the natural course of MG in 1989, in which he noted that when GMG is associated with predominant bulbar muscle weakness, it results in severe restrictions in the activities of daily life and, when severe, it can cause myasthenic crises or require respiratory assistance (23).…”
Section: Discussionmentioning
confidence: 99%
“…Significant research into the HRQL of MG has documented that psychosocial disorders, predominantly anxiety and depression, are negatively correlated with HRQL, based on multivariate linear regression analysis, apart from significant demographic predicators (older age and lower education) and the current status of myasthenia gravis. Interestingly, the Hamilton Anxiety Rating Scale was verified as a more significant prediction factor for a lower quality of life in both physical and mental aspects than the Hamilton Depression Rating Scale ( 80 82 ). Similarly, Shi's research demonstrated that anxiety, disability, fatigue and depression were independent predictors of poor HRQL in NMOSD, and that anxiety was the best predictor of both the global and physical composite scores of HRQL, followed by disability, fatigue and depression (global composite, r 2 = 0.76, P = 0.000; physical composite, r 2 = 0.71, P = 0.000) ( 32 ).…”
Section: Influencementioning
confidence: 96%